Colorimetric Picomolar-Level Determination of L-Cysteine with Fabricated N, Fe-Codoped Carbon Dots as a Peroxidase Mimic. (3rd May 2022) - Weng, Yuhui; Li, Huangjie; Zhu, Mincong; Tao, Aojia; Wang, Sha; Weng, Wen
Abstract: Novel nitrogen/iron-codoped carbon dots (N/Fe-CDs) were prepared from citric acid, ethylenediamine, and ferric chloride by a facile one-step solvothermal method and their peroxidase-like activity was evaluated. The structure and composition of the obtained carbon dots were characterized by several methods, including electron microscopy, X-ray diffraction, and spectral techniques. The presence of dopants in the particles was confirmed by X-ray photoelectron spectroscopy and inductively coupled plasma – mass spectrometry (ICP-MS). The obtained N/Fe-CDs displayed excellent peroxidase-like activity and efficiently catalyzed the oxidation of 3, 3', 5, 5'-tetramethylbenzidine in the presence of H2 O2, leading to a rapid change in the solution color from colorless to blue. Based on this reaction, H2 O2 was determined from 0 to 40 μM under optimal conditions with a detection limit of 9.0 nM. In addition, L -cysteine was shown to cause the blue color to fade. Considering this feature, a highly sensitive, fast, and specific colorimetric method was developed for L -cysteine with a detection limit of 15.8 pM, which is lower than observed in similar studies. Further, this colorimetric method was applied for the determination of L -cysteine in real samples, and the results of recovery and relative standard deviation were satisfactory. The reported catalyst can be prepared conveniently using readily available raw materials and is inexpensive, which is advantageous for its widespread application.